Green Cynicism - dimensions and effects on the purchase of ecological food products - Ham, Marija (Oeconomica Jadertina, 2019)
Numerous criticisms as well as the conspicuous number of unfair manufacturing practices in the past have led to a significant scepticism and distrust by consumers. This deeply rooted distrust, scepticism, and disinterest in some consumers, can be encompassed by the notion of green cynicism. Green cynicism significantly interferes with and disturbs all activities and efforts from the domain of sustainable marketing, given that due to the extreme distrust, it is much harder or even impossible to place the product or maintain sustainable a business entity. This leads to an aggravated acceptance of Oeconomica Jadertina 1/2019. 45 these products by consumers and slower adoption of sustainable marketing strategies by economic operators, which is undoubtedly a socially undesirable phenomenon. For this reason, it is of great importance to study and understand the factors that influence this form of cynicism and how it affects certain behaviours. This paper aims to propose and explain the concept of green cynicism and explore some of its possible dimensions and verify their impact on the intention to buy organic food products. The survey was conducted on a sample of 411 respondents from eastern Croatia representing persons who purchase most household goods. The results based on the regression analysis have shown that the strongest negative effect on intentional purchases of ecological food products is attributed to the disinterest expressed as a lack of time to contemplate these issues at all. The distrust towards the organic food products or labels that distinguish them from conventional products achieves also a significant negative impact. In this research, the impact of scepticism on the issue of the environment did not prove to be significant, which could be a consequence of the fact that it concerns a significant difference in the width of the variable range.